Selected Measurement Parameters of Water Quality: Comparative Insight of India and Indonesia - Supriyanto, Supriyanto; Koestoer, Raldi Hendro (Universitas Veteran Bangun Nusantara, 2022)
A number of rivers in India and Indonesia are usually used by the people to fulfill their daily needs. To ensure the quality of river water is in reasonable limit, it is important to monitor water quality regularly. The objective of this study was to review and compare the selection of water quality monitoring parameters in India and Indonesia. The used method was descriptive analyses. The results of the study showed several findings: first, in terms of regulation, India was lesser than that of Indonesia; second, India used the water quality index to assess the state of water quality, while Indonesia used the STORET method or the water pollution index; third, India had legally stipulated the main parameters in considering the status of water quality, whereas Indonesia had yet to stipulate it; and forth, there were 10 water quality parameters that were often used in both India and Indonesia, namely pH, BOD, COD, DO, nitrate, phosphate, temperature, TDS, TSS, and total coliform. Therefore, these parameters should be selected as the key parameters to monitor water quality.